1984
DOI: 10.1007/bf02779124
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis viruses in southern taiwan—mass survey of 2985 inhabitants

Abstract: A survey of 2985 apparently healthy Taiwanese in southern Taiwan revealed a high prevalence (18.2%) of hepatitis B surface antigen (HBsAg). It was significantly higher in males (22.3%) than in females (13.6%), but no correlation with family origin, socioeconomic status or residence was established. About one-third of the breeding female HBsAg carriers were HBeAg-positive, and these may be an important source in the spread of HBV. Subtyping of HBsAg in 63 subjects showed adw to be dominant in this area, and 8 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In this study we found the Taiwanese who were born after the implementation of nationwide disposable (Table 4), and a prevalence rate up to 98% in the age group 20 to 29 was found in blood samples collected between November 1981 and February 1982 in the study covering the whole southern Taiwan [15]. The Tainan area is in the southern part of Taiwan, and the Taipei area is in the northern part of Taiwan.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this study we found the Taiwanese who were born after the implementation of nationwide disposable (Table 4), and a prevalence rate up to 98% in the age group 20 to 29 was found in blood samples collected between November 1981 and February 1982 in the study covering the whole southern Taiwan [15]. The Tainan area is in the southern part of Taiwan, and the Taipei area is in the northern part of Taiwan.…”
Section: Discussionmentioning
confidence: 69%
“…From the review of literature, we found three studies reporting age-specific seroprevalence rates of anti-HAV IgG in the Tainan area [7,8,12], six in the Taipei area [3,4,6,[12][13][14], and one covering the whole southern Taiwan [15]. All the three studies in the Tainan area found that the seroprevalence generally increased with age, which was similar to the trends observed in the current study [6][7][8] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][12][13][14][15][16][17]23,24,[27][28][29][30][31] Prior to mass HB vaccination, Taiwan had the highest HBV infection rate in Asia. 16,24 Infants born prior to the universal HB vaccination were at high risk of being vertically infected with HBV by their mothers who were seropositive for either HBsAg or HBeAg. CHB caused by HBV is the primary risk factor for hepatocellular carcinoma (HCC), 8,25 and HCC is a major cause of death in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…doi:10.1016/j.jcv.2011.06.012 tion in Taiwan, 4,8,[14][15][16][17] Italy, 18 Malaysia, 19 South Africa, 20 and Thailand. 21,22 However, few papers have investigated the relationship between HB seroprevalence and the risk of liver bio-functions responding to vaccine.…”
Section: Objectivesmentioning
confidence: 99%
“…Taiwan is a hyperendemic area for HBV infection [16,17]. Most adults in the area have been infected by HBV during childhood.…”
Section: Introductionmentioning
confidence: 99%